Phosphorous dynamics in a temperate intertidal estuary - Lillebø, A. I. (2004)
Conservation and management of aquatic systems require detailed information of the processes that affect their functioning and development. The objectives of the present work were to describe the phosphorus dynamics during a complete tidal cycle and to quantify the relative contribution of the most common estuarine areas (e.g. seagrass beds, salt marshes, mud- and sand-flats without vegetation) to phosphorus net internal loading in a temperate intertidal estuary.